Physical Characteristics of Three Types of Muscles with Different Aging Duration - Yulianti, Karenina Dwi; Priyanto, Rudy; Nuraini, Henny (Universitas Halu Oleo, 2023)
The demand for premium quality meat continues to grow along with changes in the lifestyle of the upper middle class community, the increasing number of tourists and expatriates from abroad. The premium meat must be imported from abroad to meet the needs of special markets such as hotels, restaurants and supermarkets. Some Indonesian cattle cannot produce meat that meets the premium quality criteria, especially tenderness. The hardness of the flesh can be overcome by aging. This study aims to determine the physical and microbiological quality of bali beef with different aging times. This study used bali cattle. The treatments were aging for 1, 21 and 42 days and three different muscle types (Longisimus dorsi, Gluteus medius and Semitendinosus). This study used a completely randomized design (CRD) with a 3 x 3 factorial pattern. If the data obtained were significantly different, it would be continued with the Least Square Means test. The results showed that the combination of aging treatment for 21 days and muscle type (Longisimus dorsi, Semitendinosus) showed the best and most efficient steak tenderness results. Keywords: Bali cattle, aging, physical quality, muscle type